2017
DOI: 10.1111/jocs.13382
|View full text |Cite
|
Sign up to set email alerts
|

Pre-implant left ventricular apex position predicts risk of HeartMate II pump thrombosis

Abstract: Background Thrombosis within a Left Ventricular Assist Device (LVAD) is a devastating complication that often necessitates device exchange. Few studies have evaluated the relationship between patient anatomy and pump thrombosis. We hypothesize that lateral displacement of the left ventricular (LV) apex increases risk for pump thrombosis. Methods All patients who underwent primary implantation of a Thoratec HeartMate II (HM2) device at a single center (2009-2015) were evaluated. Operative mortalities and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It should be noted that this was a computational study, not including real patient data. Also, the left ventricular apex position is associated with the occurrence of PT [ 15 ]. There is some data on relation between LVAD angle and PT derived from pathology studies suggesting that minor thrombosis of the inflow cannula is frequently observed and unrelated to clinically relevant PT.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that this was a computational study, not including real patient data. Also, the left ventricular apex position is associated with the occurrence of PT [ 15 ]. There is some data on relation between LVAD angle and PT derived from pathology studies suggesting that minor thrombosis of the inflow cannula is frequently observed and unrelated to clinically relevant PT.…”
Section: Discussionmentioning
confidence: 99%